"PLANNING FOR THE FUTURE": A TOOL FOR PROMPTING AND RECORDING FOR ADVANCE CARE PLANNING. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Watmough, Jonathan; Gunson, Eilidh; Sheils, Rachel; Ackroyd, Rajeena
Abstract : Background: The importance of Advance Care Planning (ACP) is widely recognised. The process can increase patients' chances of achieving their preferred outcomes, prompt them to discuss concerns with their families, and help them to make realistic plans. While some patients want to write advance statements, others do not wish to discuss the future with professionals at all. Another group of patients wants to plan but does not want a patient-held document. Given patients' differing preferences regarding ACP, it would be useful for professionals to keep a record of these specific preferences, as well as broader preferences for future care. Aims: To develop a document that would (i) prompt professionals to consider ACP consistently, (ii) document the justification when ACP discussions are not offered, and (iii) provide a centralised record of outcomes of ACP discussions. To audit how many of the forms are being completed appropriately once implemented, and the outcomes of using the form. Method: We designed a proforma ("Planning for the Future") which is filed at the front of every inpatient's notes, next to any DNA CPR form. In January 2013, we audited proformas for the 55 most recent admissions. Results: Fifty-one of the 55 patient records contained the "Planning for the Future" form. Fifty one percent (26/51) recorded patients' preferred places of death, 21/51 recorded other wishes and preferences, and 24/51 forms documented formal decision making about whether or not to offer ACP. In 11 of these 24, ACP was deemed inappropriate due to impaired mental capacity or a preference not to discuss the future. Conclusions: We now have a systematic way of prompting consideration of ACP discussions, indicating whether ACP has been offered, justifying cases where it has not, and centrally documenting a patient's cumulative wishes and preferences. The proforma will be redesigned to increase its use and give our patients the best possible help in planning for the future.